Canadian Immigrant Women in Transition - Wittebrood, Gerda; Robertson, Sharon (Canadian Journal of Counselling and Psychotherapy, 2011)
The experiences of Canadian immigrant women as they move from one culture to another are examined. Making reference to relevant literature, the position of immigrant women in Canada, the barriers they encounter in their efforts to adapt to their new homeland, and the coping strategies they use to deal with these barriers are explored. In addition, the usefulness of different forms of support systems and the role of the counsellor as part of the adaptation process are examined. Immigrant women in transition represent a high-risk group in Canadian society. Elements that make them such a vulnerable group include race, language, and their roles as wives, mothers, and labourers. In addition, social, economic, and political policies in Canada contribute to an increase of gender and racial inequalities in the society. Six "transitional bridges" which immigrant women employ to make the transition from one culture to another are described. The role of the counsellor in working with these clients is explored.